Towards a Penal Law for Religious? (II/1) Consecrated Life in the Light of Pope Francis’s 2021 Reform of Book VI of the CIC: Part II. Special Considerations (1): Consecrated Life as the Object of Penal Protection, Especially Community Life - Skonieczny, Piotr (Prawo Kanoniczne, 2025)
The author analyses the discipline of religious life from the perspective of penal law in the light of Pope Francis’s recent reform of Book VI CIC/21 of 2021. The author asks whether it is possible to speak of a penal law for religious after the reform of Book VI of 2021. The second article addresses specific issues, particularly the penal protection of community life. In the general introduction, the author presents the elements of consecrated life that could be subject to penal protection, which are analysed in more detail in subsequent articles. The intensity of the presence of the various elements of consecrated life affects the level of penal protection afforded to them (I.2.). Regarding the element of community life, however, the author notes a shift from penal protection in the 1917 CIC (II.) to predominantly disciplinary protection in the 1983 CIC (III.3.1.), a change that was not reversed by Pope Francis’s reform of the 2021 CIC Book VI (III.3.2.), which only introduced penal protection to a limited extent (III.3.3.). To support this argument, the author provides a detailed analysis of the work on the CIC/83 drafts relating to community life in the broadest sense. This includes penalties that deprive the right to vote and wear the religious habit (III.1), as well as the reduction of delicts against the state and life of religious (III.2).